2021
DOI: 10.1007/978-3-030-63549-7_9
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Gender Differences in the Susceptibility to Environmental Exposures

Abstract: In the past 50 years, the number of publications on air pollution and lung disease has increased considerably, although the number of studies considering sex (a biologic factor), or gender (a social construct), has remained low and stagnant. Accumulating data from studies assessing the effects of the environment on lung health have shown direct associations of air pollution exposures with lung inflammation. Sex-specific disaggregation of data has indicated that substantialbut frequently overlookeddifferences e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 213 publications
(225 reference statements)
0
4
0
Order By: Relevance
“…In addition, our population-based evidence suggests that male may be more susceptible to PM 2.5 -induced MetS. Previous evidence has shown that there are large sex differences in the adverse effects of air pollution, but the underlying mechanisms of PM 2.5 -related MetS are still unclear [46]. Laboratory evidence suggests that hormonal differences may contribute to this difference [46,47].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In addition, our population-based evidence suggests that male may be more susceptible to PM 2.5 -induced MetS. Previous evidence has shown that there are large sex differences in the adverse effects of air pollution, but the underlying mechanisms of PM 2.5 -related MetS are still unclear [46]. Laboratory evidence suggests that hormonal differences may contribute to this difference [46,47].…”
Section: Discussionmentioning
confidence: 61%
“…Previous evidence has shown that there are large sex differences in the adverse effects of air pollution, but the underlying mechanisms of PM 2.5 -related MetS are still unclear [46]. Laboratory evidence suggests that hormonal differences may contribute to this difference [46,47]. Thereby, future experiments analysis should pay more to potential mechanisms and could help to better understand the role of PM 2.5 pollution on MetS development.…”
Section: Discussionmentioning
confidence: 99%
“…Many stressors can impact sex disparities in lung development and lung disease. These comprise indoor and outdoor air pollution, anxiety, stress associated with socioeconomic status, access to health care, genetics, epigenetics, and diet [26]. Because of their domestic roles, women are particularly exposed to household air pollution, being one particularly relevant global environmental exposure.…”
Section: Sociocultural Factors Of Women's Respiratory Diseasementioning
confidence: 99%
“…Although there are various associative studies linking adverse outcomes to co-or subsequent exposures to inhaled pollutants and viruses, causal linkages and mechanisms by which pollutant exposure may alter human respiratory response to viral infection are more limited. [4][5][6][7] The limited knowledge on how pollutants may impact response to viral infection has been acutely highlighted with the onset of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic and the resulting flurry of review articles that nicely summarize identified associations but do little to capture causal linkages. 8,9 In this article, we will focus on the impact of pollutant exposure on antiviral host defense responses and describe potential mechanisms by which pollutants can alter the viral infection cycle that have been identified through human observational and controlled exposure studies, as well as mechanistic in vitro studies.…”
mentioning
confidence: 99%